The physicochemical composition of wine elaborated from 'Sauvignon Blanc' grapevine as a result of increased bud load - Würz, Douglas André (2024)
This study aims to evaluate the effect of increasing bud load on the physicochemical composition of wine made from the 'Sauvignon Blanc' grapevine. This work was carried out during the 2016/2017 harvest in a commercial vineyard in the São Joaquim municipality, SC. The treatments consisted of four pruning levels: 15, 30, 50 and 75 buds plant-1. Six months after production, the wine samples were analyzed in triplicate for total acidity, reducing sugars, alcohol content, relative density, dry extract, ash, pH, glycerol, total polyphenols, and color. It was found that loads of 30 to 50 buds plant-1 resulted in wines with higher glycerol and pH contents with lower total acidity. The data observed for all bud loads per plant are considered adequate for quality white wines, thus indicating that it is possible to increase production rates by increasing the bud load plant-1 during winter pruning, making it more profitable for the winegrower.